3x + 24 = (3)(x) + (3)(8)
You can see that there is multiplier 3 near x and 8. You can factor it and make
3x + 24 = 3(x + 8)
So, the answer is 3. Hope this helps!
Pemdas
mutliply first
5*5=25
now we have
25+9+2+2-4+6-2-3
34+2+2-4+6-2-3
36+2-4+6-2-3
38-4+6-2-3
34+6-2-3
40-2-3
38-3
35
7/8 = 21/24
5/12 = 10/24
21/24-10/24 = 11/24
~ Simplifying
-4x + -4 = -7(x + 4)
~ Reorder the terms:
-4 + -4x = -7(x + 4)
~ Reorder the terms:
-4 + -4x = -7(4 + x)
-4 + -4x = (4 * -7 + x * -7)
-4 + -4x = (-28 + -7x)
~ Solving
-4 + -4x = -28 + -7x
~ Solving for variable 'x'.
~ Move all terms containing x to the left, all other terms to the right.
~ Add '7x' to each side of the equation.
-4 + -4x + 7x = -28 + -7x + 7x
~ Combine like terms: -4x + 7x = 3x
-4 + 3x = -28 + -7x + 7x
~ Combine like terms: -7x + 7x = 0
-4 + 3x = -28 + 0
-4 + 3x = -28
~ Add '4' to each side of the equation.
-4 + 4 + 3x = -28 + 4
~ Combine like terms: -4 + 4 = 0
0 + 3x = -28 + 4
3x = -28 + 4
~ Combine like terms: -28 + 4 = -24
3x = -24
~ Divide each side by '3'.
x = -8
~ Simplifying
x = -8
Answer:
y = 2
x = 5
Step-by-step explanation:
4x + 5y = 10 | ×3 |
3x - 3y = 21 | ×4 |
12x + 15y = 30
12x - 12y = 84
____________--
27y = -54
y = -54/27
y = 2
4x + 5y = 10 | ×3 |
3x - 3y = 21 | ×5 |
12x + 15y = 30
15x - 15y = 105
____________+
27x = 135
x = 135/27
x = 5